Structure–Property Relevance of Two Pairs of Isomeric Steviol Rebaudiosides and the Underlying Mechanism - Zhuoyu Zhou; Wanjie Wang; Qinbing Guo; Haijun Wang; Yongmei Xia (Foods)
Although enormous efforts have been made to prepare tasty and soluble steviol glycosides (SGs), the structure–property relationship of SGs still remains unclear, neither in experiment fact nor in the mechanism, such as the influence of linkage type and position of substituted glucosyl on physiochemical properties and sensory features of SGs. The favorable SGs, rebaudioside D (RD) and rebaudioside A (RA), possess good edulcorant quality, poor solubility, and other significantly different physical properties. This research chose two pairs of isomeric SGs, RA and its isomer rebaudioside E (RE) and RD and its isomer RA1G (a synthetic SG, α-1,6-mono-glucosylated RA), to conduct a comparative study, aiming to reveal the structure–property relevance on their solubility, sweetness, stability, and crystal structure. The RA1G presents an aqueous solubility 13 times that of RA and 137 times that of RD and exhibits better edulcorant quality than that of RA, similar to RD. The results indicate that the glucosyl linkage type and position have a stronger impact on the properties of the SGs than the number of glucosyl moieties. The underlying mechanism of their structure–property relevance was elucidated by analyzing the interaction energies between the SGs with solvent and human receptor proteins, respectively.